Separation and fractionation of Aquilaria Malaccensis oil using supercritical fluid extraction and the cytotoxic properties: article - Zulkifli, Mohamad Azman; Che Radzi, Nurhaslina (2017)
Aquilaria Malaccencis is a type of agarwood. This species is commonly used to extract oil. The extract oil that produces from the plant is call essential oil. The essential oil can be used in various functions. To extract oil form this plant, supercritical fluid extraction method was used. Supercritical fluid extraction is use supercritical fluid as extracting solvent. In this research CO2 was used as extraction solvent. CO2 was used because it much cheaper than other supercritical fluid. This research was carried by manipulate temperature and pressure. The temperature that was use is 30, 40, 50, 60 and 70℃. For pressure, 200, 250, 300, 350 and 400 bar was used. This pressure was selected based on literature review that was done. The optimum temperature and pressure that can produce high yield of oil is 50℃ and 400 bar respectively. From the GCMS analysis there is no arsenic wavelength in the extract oil. Therefore, there is no cytotoxic property in the extract oil. GCMS can detect all metal compounds that exist in the extract oil.